2007
DOI: 10.1186/1742-5581-4-1
|View full text |Cite
|
Sign up to set email alerts
|

Factors influencing publication choice: why faculty choose open access

Abstract: Background: In an attempt to identify motivating factors involved in decisions to publish in open access and open archives (OA) journals, individual interviews with biomedical faculty members at the University of North Carolina at Chapel Hill (UNC-Chapel Hill) and Duke University, two major research universities, were conducted. The interviews focused on faculty identified as early adopters of OA/free full-text publishing.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
88
0
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 94 publications
(98 citation statements)
references
References 13 publications
5
88
0
1
Order By: Relevance
“…[13, p. 9] Besides perceived advantages, OA usually raises some concerns too. A number of studies have demonstrated that open access publications are often considered to be of low quality and consequently less respected and prestigious than established, subscription-based journals [8,10,11,15,16,21]. However, despite perceptions of poor quality, researchers believe that publishing in OA helps career development and should not be viewed as an obstacle to tenure and promotion [11,18,21].…”
Section: Theme 3: Perceptions Of Oa Journalsmentioning
confidence: 99%
See 2 more Smart Citations
“…[13, p. 9] Besides perceived advantages, OA usually raises some concerns too. A number of studies have demonstrated that open access publications are often considered to be of low quality and consequently less respected and prestigious than established, subscription-based journals [8,10,11,15,16,21]. However, despite perceptions of poor quality, researchers believe that publishing in OA helps career development and should not be viewed as an obstacle to tenure and promotion [11,18,21].…”
Section: Theme 3: Perceptions Of Oa Journalsmentioning
confidence: 99%
“…Clearly in the mind of most scholars the strongest characteristic of OA journals is that they promote improved and more equitable access to knowledge by all kinds of readers and availability of research papers to the developing world [8,11,12,14,21]. Scholars investigated by Park & Qin [23] believed that "this advantage may promote easy acceptance and more frequent use of OA journals" (p. 72).…”
Section: Theme 3: Perceptions Of Oa Journalsmentioning
confidence: 99%
See 1 more Smart Citation
“…Instead, the project relied on a direct outreach strategy to faculty that emphasized specialized assistance in developing a cost-free course reading list as well as the strength of the library collection, such that, in nearly all cases, the actual materials included in the reading lists changed very little, if at all. The conversation around how to engage faculty in the discussion about course materials costs and, more broadly, the costs of scholarly literature in general, often addresses the problem of the misalignment of faculty incentives with low-cost or cost-free publishing models (Warlick & Vaughan, 2007;Nariani & Fernandez, 2012;Migheli & Ramello, 2013). One theory that is fairly representative of explanations of this misalignment is that of R. Preston McCafee, who analogizes faculty behavior with the economic concept of "moral hazard" (Cohen, 2008).…”
Section: Project Design and Contextmentioning
confidence: 99%
“…22 A widely accepted definition of trust is ventured by Mayer, Davis, and Schoorman, whereby trust is "the willingness of a party to be vulnerable to the actions of another party based on the expectation that the other will perform a particular action to the trustor, irrespective of the ability to monitor or control that other party." 23 Empirically, we can operationalize this as indicators that relate to the benevolence, competence, and integrity of the journal and its content.…”
Section: Literature Reviewmentioning
confidence: 99%